Preparation method and application of ternary positive electrode material

By covering the nanocomposite formed by nanometal ions and silicon ions on the surface of the ternary positive electrode material, the problem of the material being easy to react with air and electrolyte is solved, and the cycle stability and high-temperature cycle performance of the battery are significantly improved.

CN119419243AActive Publication Date: 2025-02-11HEFEI GUOXUAN HIGH TECH POWER ENERGY
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411540109.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-02-11
Estimated Expiration
2044-10-31

AI Technical Summary

Technical Problem

The ternary positive electrode material is easy to react with moisture and electrolyte in the air, resulting in poor battery circulation stability. The high-nickel ternary positive electrode material produces an irreversible phase change during the electrochemical cycle, reducing the battery discharge capacity.

Method used

A nanocomposite formed of nanometal ions and silicon ions is coated on the surface of the ternary positive electrode material. A fine and uniform coating layer is formed through hydroxyl condensation reaction and calcination steps to improve the stability and electrochemical properties of the material.

Benefits of technology

It effectively reduces the sensitivity of the material to air, reduces the reaction with the electrolyte, improves the cycle stability and high-temperature cycle performance of the battery, and extends the cycle life of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119419243A_ABST
    Figure CN119419243A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a ternary positive electrode material. The preparation method of the ternary positive electrode material provided by the invention comprises the following steps: activating nano metal ion sol; and adding a silane coupling agent, a solvent and a ternary positive electrode active material into the obtained activation solution, and carrying out hydroxyl condensation reaction and calcination to obtain the positive electrode material coated with the nano-composite formed by the metal oxide and the silicon oxide. Through double coating, the problem of poor stability of the ternary positive electrode material in the prior art can be solved under the condition that the electrical property of the material is not influenced, and residual lithium on the surface of the positive electrode material is effectively removed, so that a lithium ion battery prepared from the positive electrode material has good stability and high-temperature cyclicity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium-ion batteries, and in particular to a preparation method and application of a ternary positive electrode material. Background Art

[0002] Lithium-ion batteries have the advantages of high energy density, long cycle life, and wide operating range. Therefore, they are in great demand and attract much attention in the fields of portable electronic devices, electric vehicles, space technology, etc. As the market demand for the range of electric vehicles increases, lithium-ion batteries are required to have higher energy density, safety performance, and rate performance. However, the energy density of the current commercial cathode materials is relatively low, which limits their promotion in some fields. Therefore, improving the specific capacity and rate performance of ternary cathode materials for lithium-ion batteries has become a hot topic in current research. In response to market demand, lithium-ion battery cathode materials are mainly improved by doping, coating, and optimizing the synthesis process. Coating technology is one of the most widely used and most effective methods, that is, by coating a layer of oxide or other salt substances on the surface of the cathode material to improve its specific capacity, cycle performance, and rate performance.

[0003] Ternary cathode materials have become the most promising materials for lithium-ion battery cathode materials used in new energy vehicles due to their high platform, high specific capacity and low price. However, ternary cathode materials are prone to react with moisture in the air, which deteriorates the battery cycle stability; and the materials are prone to react with electrolytes to cause battery bulging. At the same time, the Ni produced by high-nickel ternary cathode materials during the electrochemical cycle 4+ It is easy to react with the electrolyte, produce irreversible phase change, reduce the battery discharge capacity, and deteriorate the battery cycle performance.

[0004] To solve the above problems, the researchers coated a layer of inert oxide on the surface of the ternary positive electrode material to reduce the material's sensitivity to air, reduce the reaction between the material and the electrolyte, and improve the battery's cycle stability.

[0005] For example, patent ZL201610443127.X discloses a single crystal lithium nickel cobalt manganese oxide positive electrode material obtained by high temperature sintering doping and high temperature sintering coating. Although this material has better cycle performance than the undoped coated ternary substrate, the doping and coating are achieved by solid phase high temperature sintering, the uniformity of doping and coating is poor, and the material is hard, which can easily damage the surface of the material during the crushing process, aggravating the degree of side reactions on the surface of the material and shortening the cycle life of the material.

[0006] For example, patent CN108878799A discloses a mesoporous lithium aluminum silicate-coated doped single crystal ternary positive electrode material and a preparation method thereof. Although the surface coating layer of the material has a high-speed electron channel, the problem of poor stability of the ternary positive electrode material has not yet been solved.

[0007] For example, patent CN115117318A discloses a preparation process of a mesoporous hydroxyaluminum silicon coated lithium battery positive electrode material, which includes the steps S1, preparing a hydroxyaluminum silicon coating material to obtain a mixed colloid A2, which contains a hydroxyaluminum silicon precursor; S2, spheroidization and coating, to obtain a mixed system B1, which contains a mesoporous hydroxyaluminum silicon coated lithium battery ternary positive electrode material precursor; and S3: filtration, washing, drying and calcination to obtain a mesoporous hydroxyaluminum silicon uniformly coated lithium battery ternary positive electrode material B3. The present invention uses 99.9% aluminum alkoxide, which is hydrolyzed with a silicon source and a lithium source; adds a ternary positive electrode material, refluxes and stirs to uniformly mix, spheroidizes and coats the particles; and finally calcines to obtain a mesoporous hydroxyaluminum silicon coated lithium battery positive electrode material. The product has high purity, good sphericity, and high powder specific gravity. Its energy density is 10~20% higher than that of ordinary nano-alumina coated products. The material has high surface activity and good chemical and thermal stability, but the preparation process of this material is too complicated.

[0008] In view of this, the present invention is proposed. Summary of the invention

[0009] The purpose of the present invention is to provide a method for preparing a ternary positive electrode material.

[0010] Another object of the present invention is to provide a ternary positive electrode material obtained by the above preparation method.

[0011] Another object of the present invention is to provide a lithium ion battery containing the above-mentioned ternary positive electrode material.

[0012] In order to achieve the above object, the present invention adopts the following technical solution: In a first aspect, the present invention provides a method for preparing a ternary positive electrode material, comprising the following steps: S1, activating the nano metal ion sol; S2, adding a silane coupling agent, a solvent and a ternary positive electrode active material to the activation solution obtained in step S1, calcining after a hydroxyl condensation reaction, to obtain a positive electrode material coated with a nanocomposite formed by metal oxide and silicon oxide.

[0013] The present invention selects nano metal ion sol as raw material, and after activation treatment, metal cations therein and nano silicon ions form nano composites under hydroxyl condensation reaction conditions. The activation can make it easier for hydroxyl groups to be generated on the surface of the nano metal ion sol, so that the silane coupling agent can react better after hydrolysis to form metal-O-Si-R; and then a fine and uniform coating layer is further formed under wet conditions to firmly coat the surface of the ternary positive electrode material matrix, thereby improving the unevenness problem of traditional solid phase mixing (ball milling mixing and high-mixer mixing), and effectively removing residual lithium on the surface of the positive electrode material. At the same time, the outstanding stability and excellent electrochemical activity of the metal cations and silicon ions are utilized to improve the stability and high-temperature cyclability of the ternary positive electrode material.

[0014] In the above preparation method, in step S1, the nano metal ions are selected from one or more of aluminum, zirconium, cerium and tungsten.

[0015] In the above preparation method, in step S1, the mass fraction of the nano metal ion sol is 10-30wt%, 4≤pH≤7, preferably pH4-5, and the particle size is 10-15nm.

[0016] In the above preparation method, in step S1, the total mass of metal ions in the nano metal ion sol is 0.03-0.3% of the mass of the positive electrode active material, preferably 0.15-0.3%.

[0017] In the above preparation method, in step S1, the surfactant used in the activation treatment is selected from one or more of sodium oleate, sodium laurate, hexadecyltrimethylammonium bromide, octadecyltrimethylammonium chloride, sodium dodecylbenzenesulfonate, sodium hexadecylsulfonate, potassium stearate, sodium stearate, stearic acid, sodium dodecylaminopropionate and sodium hexametaphosphate. Preferably, it is one or more of sodium dodecylbenzenesulfonate, sodium hexadecylsulfonate and sodium hexametaphosphate.

[0018] In the above preparation method, in step S1, the amount of the surfactant used is 1-5% of the mass of the nano metal ion sol, preferably 1-2%.

[0019] In the above preparation method, in step S2, the silane coupling agent is selected from one or more of methyltrimethoxysilane, vinyltrimethoxysilane, dodecyltrimethoxysilane and hexadecyltrimethoxysilane, preferably one or more of methyltrimethoxysilane and vinyltrimethoxysilane.

[0020] In the above preparation method, in step S2, the mass ratio of the silane coupling agent to the total mass of metal ions in the nano-metal ion sol is 1:(1-2).

[0021] In the above preparation method, in step S2, the solvent is ethanol.

[0022] In the above preparation method, in step S2, the mass ratio of the silane coupling agent to the solvent is 1:(1-4).

[0023] In the above preparation method, in step S2, the hydroxyl condensation reaction is carried out according to the following operation: add a silane coupling agent and a solvent to the solution obtained in step S1, react at 20-40° C. for 15-30 minutes, and then add a positive electrode active material to react for 2-4 hours.

[0024] In the above preparation method, in step S2, the calcination conditions are: in an oxygen or air atmosphere, at a temperature of 300-650° C., and for a time of 2-8 h.

[0025] In the above preparation method, in step S2, the chemical formula of the ternary positive electrode active material is LiNi x Co y Mn 1-x- y O2, 0.60≤x≤1, 0<y≤0.2.

[0026] According to a specific embodiment of the present invention, the chemical formula of the positive electrode active material is LiNi 0.88 Co 0.08 Mn 0.04 O2.

[0027] In a second aspect, the present invention also provides a ternary positive electrode material obtained by the above preparation method.

[0028] The ternary positive electrode material comprises positive electrode active material particles and a coating layer on the surface thereof; the coating layer is composed of a nano-composite formed by nano-metal ions and silicon ions.

[0029] In a third aspect, the present invention provides a lithium-ion battery, comprising a positive electrode; the material of the positive electrode is the above-mentioned ternary positive electrode material.

[0030] Compared with the prior art, the present invention has the following beneficial effects: In the present invention, metal cations and nano silicon ions form nanocomposites under hydroxyl condensation reaction conditions, and form a fine and uniform coating layer under wet conditions that is firmly coated on the surface of the ternary positive electrode material matrix, thereby improving the unevenness problem of traditional solid phase mixing (ball milling mixing and high mixer mixing), and effectively removing residual lithium on the surface of the positive electrode material. At the same time, the outstanding stability and excellent electrochemical activity of metal cations and silicon ions are utilized to improve the stability and high-temperature cyclability of the ternary positive electrode material. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1It is the SEM picture of the ternary positive electrode materials prepared in Example 1, Example 2, Comparative Example 1 and Comparative Example 2.

[0032] Figure 2 It is a comparison of room temperature cycle tests of ternary positive electrode materials prepared in Example 1, Example 2, Comparative Example 1 and Comparative Example 2.

[0033] Figure 3 It is a comparison of high temperature cycle tests of ternary positive electrode materials prepared in Example 1, Example 2, Comparative Example 1 and Comparative Example 2.

[0034] Figure 4 It is a low temperature DCR test comparison of the ternary positive electrode materials prepared in Example 1, Example 2, Comparative Example 1 and Comparative Example 2.

[0035] Figure 5 It is the capacity retention rate and capacity recovery rate of the ternary positive electrode materials prepared in Example 1, Example 2, Comparative Example 1 and Comparative Example 2 after being placed at high temperature.

[0036] Figure 6 The internal resistance growth rate and thickness change rate (expansion rate) of the ternary positive electrode materials obtained in Example 1, Example 2, Comparative Example 1 and Comparative Example 2 after being placed at high temperature. DETAILED DESCRIPTION

[0037] The present invention will be further described below in conjunction with specific embodiments, but the present invention is not limited to the following embodiments.

[0038] Unless otherwise specified, the experimental methods used in the following examples are conventional methods.

[0039] Unless otherwise specified, the reagents, materials, instruments, etc. used in the following examples can be obtained from commercial sources.

[0040] Nano aluminum sol: The particle size of the particles in the sol is 10-15nm, and it is a commercially available product.

[0041] Nano-tungsten sol: The particle size of the sol is 10-15nm, and it is a commercially available product.

[0042] Example 1 Sodium hexametaphosphate was added in a proportion of 2% to 25%wt nano-aluminum sol and nano-zirconium sol for activation treatment, and then a sol mixed activation solution was prepared according to the mass ratio of aluminum to zirconium of 1:2; The sol mixed activation solution was added to a mixture of methyltrimethoxysilane (silane coupling agent) and ethanol, wherein the mass ratio of the silane coupling agent to ethanol was 1:4, and the mass ratio of the silane coupling agent to aluminum ions was 1:2. The mixture was heated to 40°C and stirred for 5 minutes. The ternary positive electrode material LiNi was added at a mass ratio of aluminum ions to ternary positive electrode materials of 0.1:100. 0.88Co 0.08 Mn 0.04 O2, react at 40℃ for 2h; after filter pressing, washing and drying, place it in a Zhongpeng furnace and calcine at 350℃ for 5h to obtain a ternary positive electrode material double-coated with cation aluminum & zirconium and silicon ions.

[0043] Example 2 Add 1% hexadecyltrimethylammonium bromide to the 15%wt nano-tungsten sol for activation treatment to obtain a sol activation solution; The sol activation solution was added to a mixture of hexadecyltrimethoxysilane and ethanol, wherein the mass ratio of the silane coupling agent to the ethanol was 1:2, and the mass ratio of the silane coupling agent to the aluminum was 1:1. The mixture was stirred at 25°C for 30 minutes at room temperature. The ternary positive electrode material LiNi was added at a mass ratio of tungsten ions to ternary positive electrode materials of 0.15:100. 0.88 Co 0.08 Mn 0.04 O2, react at 25℃ for 4h; after filter pressing, washing and drying, place it in a Zhongpeng furnace and calcine at 650℃ for 2h to obtain a ternary positive electrode material double-coated with tungsten ions and silicon ions.

[0044] Comparative Example 1 Prepare a mixture of methyltrimethoxysilane and ethanol, wherein the mass ratio of silane coupling agent to ethanol is 1:4, heat to 40°C and stir for 5 minutes; add ternary positive electrode material LiNi according to the mass ratio of silicon ions in the silane coupling agent to the mass ratio of ternary positive electrode material to 0.05:100 0.88 Co 0.08 Mn 0.04 O2, react at 40℃ for 2h; after filter pressing, washing and drying, place it in a Zhongpeng furnace and calcine at 350℃ for 5h to obtain nano-silicon ion-coated ternary positive electrode material.

[0045] Comparative Example 2 According to the mass of aluminum ions in nano-aluminum sol and the ternary positive electrode material LiNi 0.88 Co 0.08 Mn 0.04 The mass ratio of O2 is 0.1:100 for uniform mixing. After mixing, it is placed in a Zhongpeng furnace and calcined at 350°C for 5 hours to obtain an aluminum ion-coated ternary positive electrode material.

[0046] Test Results The performance indicators of the ternary positive electrode materials obtained in Example 1 (Example 1 in the figure), Example 2 (Example 2 in the figure), Comparative Example 1 and Comparative Example 2 were tested according to the requirements of the lithium-ion battery industry specifications. The results are as follows: Depend on Figure 1 It can be seen that compared with Comparative Example 1, the surface coating of the materials obtained in Examples 1 and 2 and Comparative Example 2 is more uniform.

[0047] Depend on Figure 2-4 It can be seen that compared with Comparative Example 2, the impedance of the materials obtained after coating the surface of the ternary positive electrode material with nano-silicon in Example 1 and Example 2 increased significantly, and the room temperature cycle, high temperature cycle and capacity were all improved.

[0048] Depend on Figure 5 , 6 It can be seen that the inert metal oxide coating can effectively reduce the contact between the material and the air and electrolyte, improve the gas production problem of the battery and the thickness expansion problem of the battery when the battery is stored at high temperature, and significantly reduce the growth rate of the battery internal resistance.

[0049] Although the present invention has been described in detail above with general descriptions and specific embodiments, it is obvious to those skilled in the art that some modifications or improvements may be made thereto based on the present invention. Therefore, these modifications or improvements made without departing from the spirit of the present invention all fall within the scope of protection claimed by the present invention.

Claims

1. A method for preparing a ternary positive electrode material, comprising the following steps: S1, activating the nano metal ion sol; S2, adding a silane coupling agent, a solvent and a ternary positive electrode active material to the activation solution obtained in step S1, calcining after a hydroxyl condensation reaction, to obtain a positive electrode material coated with a nanocomposite formed by metal oxide and silicon oxide.

2. The preparation method according to claim 1, characterized in that: In step S1, the nano metal ions are selected from one or more of aluminum, zirconium, cerium and tungsten; The mass fraction of the nano metal ion sol is 10-30wt%, 4≤pH≤7, and the particle size is 10-15nm; The total mass of metal ions in the nano-metal ion sol is 0.03-0.3% of the mass of the ternary positive electrode active material.

3. The preparation method according to claim 1 or 2, characterized in that: In step S1, the surfactant used in the activation treatment is selected from one or more of sodium oleate, sodium laurate, hexadecyltrimethylammonium bromide, octadecyltrimethylammonium chloride, sodium dodecylbenzenesulfonate, sodium hexadecylsulfonate, potassium stearate, sodium stearate, stearic acid, sodium dodecylaminopropionate and sodium hexametaphosphate; The dosage of the surfactant is 1-5% of the mass of the nano metal ion sol.

4. The preparation method according to any one of claims 1 to 3, characterized in that: In step S2, the silane coupling agent is selected from one or more of methyltrimethoxysilane, vinyltrimethoxysilane, dodecyltrimethoxysilane and hexadecyltrimethoxysilane; The mass ratio of the silane coupling agent to the total mass of metal ions in the nano-metal ion sol is 1:(1-2); The solvent is ethanol; The mass ratio of the silane coupling agent to the solvent is 1:(1-4).

5. The preparation method according to any one of claims 1 to 4, characterized in that: In step S2, the hydroxyl condensation reaction is carried out according to the following operation: add a silane coupling agent and a solvent to the activation solution obtained in step S1, react at 20-40° C. for 15-30 minutes, and then add a positive electrode active material to react for 2-4 hours.

6. The preparation method according to any one of claims 1 to 5, characterized in that: In step S2, the calcination conditions are: in an oxygen or air atmosphere, at a temperature of 300-650° C., for a time of 2-8 hours.

7. The preparation method according to any one of claims 1 to 6, characterized in that: In step S2, the chemical formula of the ternary positive electrode active material is LiNi x Co y Mn 1-x-y O2, 0.60≤x≤1, 0<y≤0.

2.

8. The ternary positive electrode material obtained by the preparation method according to any one of claims 1 to 7.

9. A lithium-ion battery comprising a positive electrode; the material of the positive electrode is the ternary positive electrode material according to claim 8.

Citation Information

Patent Citations

  • Doped micro-scale single-crystal ternary positive electrode material and preparation method thereof

    CN105932321A

  • Mesoporous lithium aluminum silicate coated doped single crystal ternary positive electrode material and preparation method thereof

    CN108878799A

  • Carbon solid acid and aluminic acid ester doped ferric fluoride anode material with titanium-phosphate-lithium three-component surface modification, and preparation method of anode material

    CN103682267A

  • Preparation method of silicon-coated modified ternary cathode material

    CN109473671A

  • Titanium-doped porous ternary material and preparation method thereof, half battery and lithium ion battery

    CN114050240A